Mode of Delivery Determines Neonatal Pharyngeal Bacterial Composition and Early Intestinal Colonization. Issue 3 (September 2016) - Brumbaugh, David E.; Arruda, Jaime; Robbins, Kristen; Ir, Diana; Santorico, Stephanie A.; Robertson, Charles E.; Frank, Daniel N.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Bacterial colonization and succession of the human intestine shape development of immune function and risk for allergic disease, yet these processes remain poorly understood. We investigated the relations between delivery mode, initial bacterial inoculation of the infant oropharynx (OP), and intestinal colonization. Methods: We prospectively collected maternal rectal and vaginal swabs, infant OP aspirates, and infant stool from 23 healthy mother/infant pairs delivering by cesarean (CS) or vaginal delivery (VD) in an academic hospital. Bacterial abundance (16S rRNA sequencing) and community similarity between samples were compared by delivery mode. Shotgun DNA metagenomic sequencing of infant stool was performed. Results: VD infants had higher abundance of Firmicutes (mainly lactobacilli) in OP aspirates whereas CS OP aspirates were enriched in skin bacteria. OP aspirates were more similar to maternal vaginal and rectal microbiomes in VD compared with CS. Bacteroidetes were more abundant through 6 weeks in stool of VD infants. Infant fecal microbiomes in both delivery groups did not resemble maternal rectal or vaginal microbiomes. Differences in fecal bacterial gene potential between CS and VD at 6 weeks clustered in metabolic pathways and were mediated by abundance of Proteobacteria and Bacteroidetes. Conclusions: CS infants exhibited different microbiota in the oral inoculum, a chaotic pattern of bacterial succession, and a persistent deficit of intestinal Bacteroidetes. Pioneer OP bacteria transferred from maternal vaginal and intestinal communities were not prominent constituents of the early infant fecal microbiome. Oral inoculation at birth may impact the intestinal microenvironment, thereby modulating early succession of intestinal bacteria.